2018
DOI: 10.3758/s13414-018-1633-5
|View full text |Cite
|
Sign up to set email alerts
|

Which task will we choose first? Precrastination and cognitive load in task ordering

Abstract: Precrastination, as opposed to procrastination, is the tendency to embark on tasks as soon as possible,evenat the expense of extra physical effort. We examined the generality of this recently discovered phenomenon by extending the methods used to study it, mainly to test the hypothesis that precrastination is motivated by cognitive load reduction. Our participants picked up two objects and brought them back together. Participants in Experiment 1 demonstrated precrastination by picking up the near object first,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 40 publications
9
45
1
Order By: Relevance
“…Thus, we suggest that our participants were biased to make free choices that minimized cognitive effort. This is consistent with research on decision making that shows that participants will tend to make choices, even choices that appear suboptimal, that conserve cognitive effort (Botvinick & Rosen, 2009;Dignath, Kiesel, & Eder, 2015;Fournier et al, 2019;Kool et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, we suggest that our participants were biased to make free choices that minimized cognitive effort. This is consistent with research on decision making that shows that participants will tend to make choices, even choices that appear suboptimal, that conserve cognitive effort (Botvinick & Rosen, 2009;Dignath, Kiesel, & Eder, 2015;Fournier et al, 2019;Kool et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Research indicates that people tend to avoid choices that require more cognitive effort (Ballard, Hayhoe, & Pelz, 1995;Droll & Hayhoe, 2007;Dunn, Lutes, & Risko, 2016). Even for decisions that require few demands on cognition, the less cognitively effortful alternative is typically chosen (e.g., Fournier et al, 2019;Kool, McGuire, Rosen, & Botvinick, 2010) and may be more rewarding (Botvinick, Huffstetler, & McGuire, 2009;Botvinick & Rosen, 2009). Thus, if any response biases exist in selecting free-choice responses, we would expect to find a bias that circumvents partial feature overlap with the future action goal.…”
Section: Introductionmentioning
confidence: 98%
“…Premature switching was also observed when the continuous mode was the first mode and the discrete mode was the second. In other work, Levy-Tzedek (2017) showed, much as Fournier et al (2019) did, that adding a cognitive task (counting backward) affected the likelihood of precrastination. Levy-Tzedek (2017) also found that older adults precrastinated less than younger adults, for reasons still to be explored.…”
Section: Precrastination Reduces Cognitive Demandsmentioning
confidence: 83%
“…In another experiment, Fournier et al (2019) gave participants a memorization task in conjunction with less attention-demanding object carrying. These participants precrastinated at higher rates than participants who were not given the added memorization.…”
Section: Precrastination Reduces Cognitive Demandsmentioning
confidence: 99%
“…Results from young individuals performing the implicit switching task [9] as well as from studies of pre-crastination (e.g., [70,71]) and of predictive control of saccadic eye movements [72] suggest that there is a cognitive component to the predictive control of movement. The cognitive decline reported to be associated with PD [4] would suggest we should find less predictive control in the PD population, but that is not the case, potentially due to the dopaminergic medication they take, as suggested above.…”
Section: Predictive Control Of Movementmentioning
confidence: 99%